HADITS LUGAWῙ SEBAGAI METODE DALAM PENAFSIRAN HADITS - Ahmad Sudianto; Fatihatun Nadliroh (AL-BAYAN INSTITUTE, 2022)
The lugawī hadith style is an inseparable part of the hadith interpretation methodology. This style is presented as an effort by the scholars to reveal the meanings of the Nabawi kalam which has high literary value. This article was written to examine the lugawī hadith style and examples of its application in manifesting the Prophet's messages. This study was written using the bibliographic method through exploration of authoritative references and approaches to religious texts. The approach in question is applied in order to distance researchers from being subjective, thus harming the validity of the research. The research results show that the lugawī hadith style encourages understanding the meaning of alfāẓ al-garībah, majāzāt wa al-ḥaqā'iq and asbāb al-wurūd as well as appreciation of the meaning of texts that contain essential values.